Contextual Electronics Learning Module in Sociology Learning at Senior High School - Baeng, Benediktus; Situmorang, Robinson; Winarsih, Murni (Journal of Education Reseach and Evaluation, 2022)
The low achievement of student learning outcomes in sociology learning is caused by student learning difficulties. This learning difficulty is caused by limited contextual learning resources. One solution to overcome these learning difficulties is to use contextually based sociology e-modules. This study aims to develop sociology learning e-modules based on a contextual learning approach, especially with the context of East Nusa Tenggara society. This research is a Research and Development (R&D) developed using the Dick and Careys model which is integrated with Hannafin and Peck. Data collection methods are carried out by observation, interviews and questionnaires. Methods of data analysis carried out qualitatively and quantitatively. This study involved teachers, experts and students of class XI IPS as users of the e-module. The results of the study show that the Sociology E-module is declared feasible based on the assessment of experts. The sociology e-module received good ratings by learning design experts, very good by material experts, and very good by media experts. The user response also gives a very good assessment of the E-module. Based on the results of effectiveness testing, the sociology e-module is effective in improving student learning outcomes. This research contributes to sociology learning based on the context of East Nusa Tenggara society.